Silver nanoparticles deposited on pyrogenic silica solids: Preparation and textural properties - M Zienkiewicz-Strzałka; M Błachnio; A Deryło-Marczewska; RB Kozakevych; YM Bolbukh; VA Tertykh (Adsorption Science & Technology)
Silver-based nanomaterials and composites are important components in materials science and engineering due to the reactivity of silver nanophase based on exceptional surface effects. Ag-doped SiO 2 nanocomposites were synthesized by wet impregnation procedure of aminopropyl-functionalized silica materials with submicrometer structure. Aminopropyl-functionalized pyrogenic silicon dioxide with amount of amino groups established as half and close to full monolayer was used to immobilize the nanosilver phase obtained from ammoniacal silver complex as a noble metal precursor. Pyrogenic silicon dioxide as an inexpensive nanostructured material with useful properties including adsorptive affinity for noble metal ions and organic macromolecules was applied as a support for diamminesilver(I) ions and finally for silver nanoparticles. In the present study, the effect of amino-functionalization and silver nanoparticles deposition was monitored by investigation of the textural properties and thermal stability of obtained nanocomposites. The properties of the nanocomposites were investigated by transmission electron microscopy, nitrogen adsorption–desorption isotherms, and thermal analysis (thermogravimetry/differential scanning calorimetry).